2005
DOI: 10.1002/chem.200400814
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Heterofullerene Stabilities: A Combined DFT and Chemometric Study of C56Pt2, C57Pt2and C81Pt2

Abstract: A systematic search of the regioisomers of the heterofullerenes, C57Pt2 and C56Pt2, has been carried out by means of density functional calculations to find the most stable structures. Both heterofullerenes incorporate two metal atoms into the fullerene surface. In the case of C57Pt2, one platinum atom substitutes one carbon atom of C60 and the other platinum atom replaces a C--C bond, whereas in C56Pt2 each platinum atom replaces one C--C bond. Several geometric factors were studied, three of which have parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…9,10,35,36 Changgeng et al 36 studied several metallofullerenes, not including platinum, by using the local spin density approximation and found structures similar to what other studies, including this one, find for a platinum heterofullerene. Poblet et al, 10 Hayashi et al, 9 and Campanera et al 35 used DFT within various versions of the program ADF. [37][38][39] 3.1.1 The formation of C 59 Pt.…”
Section: The Stability Of C 59 Ptsupporting
confidence: 61%
“…9,10,35,36 Changgeng et al 36 studied several metallofullerenes, not including platinum, by using the local spin density approximation and found structures similar to what other studies, including this one, find for a platinum heterofullerene. Poblet et al, 10 Hayashi et al, 9 and Campanera et al 35 used DFT within various versions of the program ADF. [37][38][39] 3.1.1 The formation of C 59 Pt.…”
Section: The Stability Of C 59 Ptsupporting
confidence: 61%
“…A range of C 59 M compounds of group 6-8 metals were predicted by DFT studies reported by Jensen's group 8 to have sufficient stability for experimental observation. Campanera et al 9 have performed a systematic search of the regioisomers of the heterofullerenes C 57 Pt 2 and C 56 Pt 2 by means of density functional calculations to nd the most stable structures. They found that the deformation of the carbon framework was a general factor for governing the relative stabilities of the regioisomers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the synthesis of second-and third-row transition metal-doped fullerenes has been predicted to be attainable via reaction of the corresponding transition metal trichloride (or dichloride) in the presence of chlorine gas (Cl 2 ) and buckminsterfullerene (C 60 ) [105]. Theoretical studies also provide insight into the electronic properties of transition metal-doped fullerenes [106][107][108][109]. In general, the energy gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) in transition metal-doped fullerenes decreases in comparison to the parent fullerene upon introduction of a transition metal atom into the cage [109], resulting in higher conductivity and reactivity [106], and hence suggests similar effects for nanotubes.…”
Section: Introductionmentioning
confidence: 99%